EFEKTIVITAS LEMBAGA PENJAMIN SIMPANAN DALAM MELINDUNGI DANA NASABAH PERBANKAN DI INDONESIA - Sheila Aida Fitriani; Baidhowi Baidhowi (JURNAL ILMIAH NUSANTARA, 2025)
. In response to the financial crisis that hit Indonesia in the late 1990s, the Deposit Insurance Agency (LPS) was established based on Law Number 24 of 2004. The main objective of LPS is to maintain the integrity of the national financial system and protect consumers by providing deposit guarantees. This study aims to assess the extent to which the role of LPS in handling bankrupt banks and guaranteeing consumer funds has been implemented, especially considering the difficulties caused by the digital transformation in the banking industry. This study examines several laws and regulations and how the LPS function is implemented in practice using normative legal research methodology and regulatory regulation methodology. The research findings show that LPS has succeeded in carrying out its strategic tasks, including processing claims in a timely, transparent, and coordinated manner with authorities including the OJK and Bank Indonesia. However, there are still difficulties, especially in terms of managing the dynamics of digital banks, the increasing threat of cybercrime, the complexity of deposit products, and shortcomings in institutional capacity and public education. Therefore, LPS must update the laws and regulations on guarantees, increase socialization to the public, and improve technical readiness. This action is necessary to ensure that LPS can continue to protect customer funds as effectively as possible and actively contribute to maintaining the stability and trust of the banking system in the digital era.